PANEKTOMI TOTAL PADA PRIA 66 TAHUN DENGAN KARSINOMA SEL SKUAMOSA PADA PENIS - Hatta, Rezky Darmawan; Hutapea, Richard (Media Dermato-Venereologica Indonesiana, 2024)
Introduction: Squamous cell carcinoma (SCC) of the penis is a rare malignancy originating from the epithelial cells of the inner prepuce or glans penis. The most common feature is the presence of a visible and palpable lesion on the penis, which is accompanied by pain, discharge, bleeding, or foul odor. Case report: A 66-year-old man came to the skin and genital clinic of Adam Malik Hospital with complaint of a lump in the penis which had been getting bigger since 3 months ago. Since 5 months ago the patient complained of sticky and painful foreskin on the penis. There was no history of trauma or warts. The patient is not circumcised and a heavy smoker. Discussion: Not circumcised are one of the risk factors for an increased incidence of malignancy of the penis. SCC of the penis has a predictable pattern of metastases, with regional lymph nodes appearing first, followed by deep lymph nodes and then distant metastases. The results of the pathology examination showed the presence of cancer cells originating from the squamous epithelium that were still well differentiated. This examination can determine the type of cell, the degree of pathology, involvement of the corpora cavernosa, corpora spongiosum, inguinal lymph nodes to cancer-free determination at the proximal border of the penectomy incision. Conclusion: Penile cancer is a cancer that has many risk factors. Patients who have been diagnosed with penile cancer, the treatment chosen is a total or partial penectomy depending on the area of ​​the affected tissue